Implantação de campos e propostas de gerenciamento da coleção de etnologia do Museu Câmara Cascudo/UFRN no Sistema ACERVUS/UFRN - Medeiros, Jailma da Silva (2018)
This work consists of a research on the management of museum collections. The objective was to implement fields in the ACERVUS System to catalog the Collection of Ethnology of the Museu Câmara Cascudo (MCC) of the Universidade Federal do Rio Grande do Norte (UFRN). Other processes have also been suggested that allow an adequate management of this patrimony. For this, it was anchored mainly in museological norms and policies. The ACERVUS System was developed by the IT Superintendence of UFRN and allows the inclusion of fields according to the needs of each collection. In order for these interventions to be in line with the requirements of Information Management and museological principles, the following actions have been carried out: analysis of legislation, guidelines and standards related to these themes; documentary and flow survey of the MCC Collection of Ethnology and conducting interviews in the focus group format. The idea was to discuss the informational needs and, thus, to contribute more assertively to the improvement of the ACERVUS System. These procedures were guided by the actionresearch methodology. In this method, the researcher is concomitantly participating in the research and, in turn, seeks to solve or clarify proposed problems in the observed situation. As theoretical support, authors were researched dealing with information management, information systems and collections management. The main difficulty found in this work was the fact that all the objects of this study were in the phase of implantation, restructuring or transformation. As results, the fields in the ACERVUS System for cataloging the MCC Collection of Ethnology were effectively created. Proposals were also made to enable the management of collections according to the recommendations of the International Committee of Museums of the International Council of Museums. It is hoped that this research contributes to give greater accessibility to UFRN's collections.